2019
DOI: 10.1609/hcomp.v7i1.5272
|View full text |Cite
|
Sign up to set email alerts
|

Second Opinion: Supporting Last-Mile Person Identification with Crowdsourcing and Face Recognition

Abstract: As AI-based face recognition technologies are increasingly adopted for high-stakes applications like locating suspected criminals, public concerns about the accuracy of these technologies have grown as well. These technologies often present a human expert with a shortlist of high-confidence candidate faces from which the expert must select correct match(es) while avoiding false positives, which we term the “last-mile problem.” We propose Second Opinion, a web-based software tool that employs a novel crowdsourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…For instance, Otterbacher et al (2019) show how cognitive biases and stereotypes can affect image labeling and Peng et al (2019) discuss at length how cognitive biases may affect the hiring process. Mohanty et al (2019) and Kemmer et al (2020) acknowledge that a variety of biases such as the confirmation bias can lead to low-quality data labels and propose methods to mitigate these effects.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Otterbacher et al (2019) show how cognitive biases and stereotypes can affect image labeling and Peng et al (2019) discuss at length how cognitive biases may affect the hiring process. Mohanty et al (2019) and Kemmer et al (2020) acknowledge that a variety of biases such as the confirmation bias can lead to low-quality data labels and propose methods to mitigate these effects.…”
Section: Resultsmentioning
confidence: 99%
“…Accuracy-focused tasks have one correct answer. Some crowdsourcing papers in this space include TurKit [93] and Second Opinion [109]. Examples of these tasks include math problems [38,88,101,145,158], blurry text recognition [92,93], and matching images with the same content [74,109].…”
Section: Outcomementioning
confidence: 99%
“…Simplifying tasks can increase quality [28,83,120,142]. Another strategy is to adapt the subtask to fit the worker's capabilities [12,23,109,120]. For example, researchers found that crowdworkers were better at generating predictive features than at estimating if a feature is predictive; so they adapted the workflow accordingly [25].…”
Section: Response Diversitymentioning
confidence: 99%
See 2 more Smart Citations